Economic reform and promoting private sector development in Iraq - Suad Qasim Hashem Al-Musawi (Iraqi Journal for Administrative Sciences, 2025)
There is no doubt that the trends of the Iraqi state at the current stage began moving towards the correct paths Iraqi economy and by focusing on the process of restructuring the Iraqi economy, which has suffered throughout the eighties and nineties and the beginning of the new millennium of economic problems, many tended to worsen rather than treatment after years of change epitaxial Since 2003 until now, and most important of these problems is the decline in the contribution of the private sector in the national economy, but some go that this sector has ended completely after 2003, following the policy of opening the doors to the importation of foreign goods Mmadjal local product uncompetitive in addition to the lack of political instability and insecurity and the targeting of businessmen and their families kidnapping or murder, which led to the escape of private capital to neighboring countries in search of investment opportunities for theirmoney,andstability. The restructuring of the Iraqi economy requires radical reform and the level of economic sectors all, including the private sector through the development of plans based on the activation of the mechanism of the free market and reduce the role of the state in economic activity and making the private sector the focus of development and a pioneer in assumed responsibility for reconstruction and play a bigger role on the Square economy Iraq to promote the principles of free economy through to enable the supply of the necessary supplies for reconstruction and organizing participation in contracts and tenders to be raised to be a major actor to take on the functions of the implementation of these contracts. Find premise: Search starts from the premise basis that irrational trends of the economic policies adopted by the State towards the private sector had a significant impact in تلكوء growth and poor performance and declining contribution to the growth of the Iraqi economy. Objective of this research: To highlight the reality of the private industrial sector and rationale for the decline of its contribution to the economy and the policies and mechanisms needed to promote it in light of the new economic trends and aspiring to work with the market mechanism. Research Methodology: In order to achieve the objectives of the research and validate his hypothesis was use of the historical method descriptive knowledge of the role of the private sector in the Iraqi economy in the stages of its historical development, then use the analytical method for the purpose of knowledge of the reality of the private sector and the impact of changes in the Iraqi economy and the reality of this sector, and use the curriculum forward-looking Machinery required for advancement.